Investigation of anti-nociceptive, anti-inflammatory potential and ADMET studies of pure compounds isolated from Isodon rugosus Wall. ex Benth - Alshehri, Osama M.; Zeb, Anwar; Mukarram Shah, Syed Muhammad; Mahnashi, Mater H.; Asiri, Saeed Ahmed; Alqahtani, Omaish; Sadiq, Abdul; Ibrar, Muhammad; Alshamrani, Saleh; Jan, Muhammad Saeed (Frontiers in Pharmacology, 2024)
The strong ethnopharmacological utilization of Isodon rugosus Wall. Ex. Benth in several types of pain and inflammation including; toothache, earache, abdominal pain, gastric pain and generalized body pain and inflammation. Based on this background the antinociceptive effect of crude extract, various fractions and essential oil has been reported previously. In this research work we isolate, characterize the pure bioactive compounds from I. rugosus and to evaluate possible mechanism following various in-vivo and in-vitro models. The pure compounds were analyzed for analgesic and anti-inflammatory activity through various assays. The column chromatography of chloroform fraction of I. rugosus has covered the identification of two pure compounds i.e, 1and 2. In which compound 1 demonstrated notable inhibition (62 % writhing inhibition, 72.77 % COX-2 inhibition, 76.97 % 5-LOX inhibition) and anti-inflammatory potential (> 50 % paw edema inhibition at various intervals). The possible mechanism involved in the antinociception was considered as central, a concept that already has been elucidated through application of naloxone (antagonist of opioid receptors). The adrenergic receptor involvement was checked out via hotplate model (adrenergic receptor antagonist). The strong ethnomedicinal analgesic background of I. rugosus, previous reports and current observations, leads to a conclusion that I.rugosus is a potential source of antinociceptive and antiinflammatory bioactive compounds. It may conclude from the results that the isolated analgesic compounds of I.rugosus may be a possible alternative remedy for pain and inflammation management with admirable efficacy and safety profile.